Keterlibatan Pria Dalam Iklan Produk Kecantikan di Indonesia: Kajian Makna Ideasional - Baehaqi, Jihan Fakhria; Gunawan, Wawan (MEDIASI Jurnal Kajian dan Terapan Media, Bahasa, Komunikasi, 2025)
This study aims to identify the involvement of men in beauty advertisements in Indonesia, both visually and verbally, using the Systemic Functional Linguistics (SFL) approach and multimodal analysis. Data were collected from the Instagram accounts of four leading beauty brands: Somethinc, Azarine, Skintific, and Scarlett Whitening. The analysis focuses on visual and verbal elements to explore ideational meanings in the representation of men in advertisements. The findings reveal that most advertisements feature male models as the main actors through narrative processes that emphasize the benefits of the product as a solution to audience needs. Material and relational processes dominate, reinforcing positive associations with the product, as reflected in verbal claims such as "brightens the skin." Additionally, the use of foreign languages and modern design elements highlights the product's global image and exclusivity, while positioning men as active consumers of beauty products. This study contributes to the study of gender representation in advertisements and provides insights for advertising practitioners to optimize communication effectiveness through visual and verbal elements. These findings are expected to offer valuable insights for gender-based marketing strategies in both local and global markets.